Evaluation of Risk on Cardiovascular Problem Reoccurrence by Assessing the Prescription and Lifestyle Modifications: A Cross-Sectional Study - Battula, Pradeep; Narapureddy, Akhila; Ammireddy, Pavithra; Mulla, Abdul Haseeb; Shaik, Karishma Khyder; Basha, Mulla Saddar; Krishna, Setlem Venkata Sai; Perla, Venkata Chenchaiah (Indian Journal of Pharmacy Practice)
Objectives: To determine the risk of reoccurrence in CVD patients based on questionnaire, drug interactions and ejection fraction. Materials and Methods: It was a cross-sectional hospital-based observational study. The study questionnaire contains qualitative and quantitative queries. The obtained score decides whether the patient is mild, moderate, or severe. Results: Out of 211 patients, according to the questionnaire, six patients (2.84%) had severe risk, 59 individuals (27.9%) were at risk according to the American Heart Association’s Ejection Fraction recommendations. Four individuals (1.8%) were more at risk based on the drug interactions. Furthermore, alcohol (OR=5.06, 95% CI=1.03 -24.78), palm oil (OR=13.14, 95% CI=0.9-191.23), sunflower oil (OR=3.53, 95% CI=0.33-37.52), buffalo milk (OR=3.58, 95% CI=0-7,845.56), and a lack of exercise (OR=7.64, 95% CI=2.43-24.04) were the main risk factors for the development of CVD disease. Further smoking (χ2=17.21, p=0.001), passive smoking (χ2=6.37, p=0.012), alcohol (χ2=12.59, p=0.001), cooking oil (χ2=9.5, p=0.009), junk food (χ2=7.58, p=0.006), lack of exercise (χ2=13.65, p=0.001), eating more sodium in foods (χ2=5.77, p=0.016), and blood cholesterol (χ2=5.12, p=0.024), have association with risk of CVD. Conclusion: Lifestyle modifications need to be followed to reduce the progression of CVD; otherwise, the patients are at risk of developing CVD disease.
Keywords: Cardiovascular disease; Ejection fraction; Lifestyle modifications; Cardiac risk assessment; Potential drug interactions